2005
DOI: 10.1111/j.1532-5415.2005.53268.x
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Barriers to Trying Self‐Management Approaches for Chronic Pain in Older Persons

Abstract: Older primary care patients with chronic pain are willing to try exercise and relaxation therapies to help manage pain but report a substantial number of barriers to participating in these programs. Addressing patient-level barriers could improve engagement in and adherence to exercise and relaxation therapies for managing pain in older persons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 21 publications
(33 reference statements)
3
54
0
Order By: Relevance
“…Some previous studies have sought to identify barriers to self-management of chronic conditions with both patients 36,37 and GPs, 18 and more specifically chronic pain in older people, 38 and those with comorbid depression. 39 The findings of the current study concur with much of this earlier work.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Some previous studies have sought to identify barriers to self-management of chronic conditions with both patients 36,37 and GPs, 18 and more specifically chronic pain in older people, 38 and those with comorbid depression. 39 The findings of the current study concur with much of this earlier work.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…When designing home-based exercise programmes, home-visiting nurses need to focus on patients' compliance with behavioural changes towards pain relief. Thus, nurses may provide exercise programmes using a pamphlet with big pictures of each body movement for patients to easily learn and practice on a daily basis (Austrian et al, 2005;Park et al, 2013).…”
Section: Organizational Barriersmentioning
confidence: 99%
“…Most previous studies examined barriers to chronic pain management in institutional settings such as hospitals and nursing homes (Gudmannsdottir & Halldorsdottir, 2009;Teh et al, 2009;Wilsey et al, 2008), and patients' perspectives (Austrian, Kerns, & Reid, 2005;Davis et al, 2002;Dima et al, 2013;Gudmannsdottir & Halldorsdottir, 2009;Lansbury, 2000;Park et al, 2013;Teh et al, 2009), rather than nurses' perspectives. There is an urgent need for more investigation of the barriers nurses perceive when caring for older adults with chronic pain in community settings (Dewar, 2006;Teh et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It results mostly in lack of information by healthcare professionals about pain control of older people. Furthermore, extensive documentation requirement may deter health-care professionals from appropriately prescribing effective treatments [39,40]. Other factors such as inadequate reimbursement and financial incentives for pain management efforts, negative reinforcement in training programs for attending to pain while being rewarded for less important and more detailed interventions, lack of training for pain management skills, lack of recognition and interaction among various medical disciplines (and even among different pain groups), limited access to diagnostic or therapeutic facilities or experts, inadequate pharmacy services, insufficient staffing for proper pain assessment and interventions, inflexible access to medications based on formulary selections, and other restrictive policies may also contribute to failure in treatment of pain [4,40].…”
Section: Ineffective Management Of Chronic Musculoskeletal Pain In Olmentioning
confidence: 99%
“…Generally older adults are interested in self-managing their chronic pain but can't find opportunity. Austrian et al indicated that 73% of the 68 patients (70 years of age and over with chronic pain) included in his study were willing to participate in an exercise program for pain management but 16% of them had this opportunity [40].…”
Section: Exercise Adherence In Older Adults With Chronic Musculoskelementioning
confidence: 99%